Development of Work Discipline, Compensation and Environment Work on the Performance of Employees of Smec Tempe Soleh Factory - Zaki Rahadian; Devana Angela Putri Erintasya; Dwi Epty Hidayaty (Formosa Journal of Science and Technology, 2023)
Tempe Soleh is a food company engaged in the processing of heavy food which is located at Jl. Kp. West Sukaseuri No. 74, Kota Baru, Kec. Kota Baru, Karawang, West Java. These MSMEs have not been able to produce Production Employee Performance due to a lack of knowledge in Employee Performance. Therefore, efforts to overcome these problems in this study will drain a good load and most employees are disciplined at work, but the performance of these employees is still below standard. The factory industry provides employees with sufficient wages and benefits, but their performance is still far from expectations and unable to fulfill orders. The work environment has been designed to make employees feel comfortable, but their performance is also subpar. (1) Does work discipline affect the performance of employees in the Tempe Bapa soleh craftsman home industry? Thus the formulation of the case study. 2) What is the effect of wages on the exhibition of MSME workers in the Tempe Bapa soleh processing factory. (3) How does the work zone of the Ayah Soleh UMKM Tempe Factory affect employee performance? 4) How is the performance of employees at the UMKM Tempe Factory Bapa Soleh influenced by the work zone, safety and work discipline simultaneously